STUDI KOMPARATIF PENGGUNAAN MEDIA POP-UP BOOK DIGITAL CERITA “LEGENDA DANAU KERINCI: CALUNGGA DAN CALUPAT” DAN E-BOOK PADA SISWA SMP - Zelahayani; Yusra D; Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has encouraged the use of more innovative learning media in Indonesian language learning at the Junior High School (SMP) level, especially in learning folklore that requires an understanding of the storyline, characters, and cultural values. This study aims to compare student learning outcomes between the use of E-Book media and digital Pop-Up Book media in learning the folklore "Legend of Lake Kerinci: Calungga and Calupat". This study uses a quantitative approach with a comparative study design. The subjects of the study were 28 students of class VII C of SMP Negeri 7 Muaro Jambi. The same students participated in two learning sessions with different treatments, namely learning using E-Book media and learning using digital Pop-Up Book media. Data collection was carried out through learning outcome tests (posttests) given after each treatment, then analyzed using descriptive and comparative statistical analysis. The results of the study showed that there were significant differences in learning outcomes between the two media, where the posttest results of students after using digital Pop-Up Book media were higher than those using E-Book media. This indicates that digital Pop-Up Book media is more effective in increasing students' attention, engagement, and understanding of the content of folktales and their cultural values.